2011
DOI: 10.1002/cjoc.201180249
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Phase Hydrogenolysis of Biomass‐derived Lactate to 1,2‐Propanediol over Silica Supported Cobalt Nanocatalyst

Abstract: Liquid phase hydrogenolysis of ethyl lactate to 1,2-propanediol was performed over silica supporting cobalt catalysts prepared by two different methods: precipitation-gel (PG) technique and deposition-precipitation (DP) procedure. The cobalt species (Co 3 O 4 /cobalt phyllosilicate) present in the corresponding calcined PG and DP catalysts were different as a consequence of the preparation methods, and Co-OH-Co olation and Si-O-Co oxolation molecular mechanisms were employed to elucidate the chemical phenomena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…This revealed that Zn, Fe, Cu, and Sn in Co-containing catalysts accelerated the formation of cobalt(II) silicate. On the basis of our results and previously reported results for similar cobalt-based catalysts [15,17,26], we propose that both Co 3 O 4 and cobalt phyllosilicate were present on the surface of the bimetallic catalysts. The absence of cobalt phyllosilicate diffraction peaks from the XRD patterns may have been due to the amorphous structure of this species.…”
Section: Xps Analysissupporting
confidence: 85%
See 3 more Smart Citations
“…This revealed that Zn, Fe, Cu, and Sn in Co-containing catalysts accelerated the formation of cobalt(II) silicate. On the basis of our results and previously reported results for similar cobalt-based catalysts [15,17,26], we propose that both Co 3 O 4 and cobalt phyllosilicate were present on the surface of the bimetallic catalysts. The absence of cobalt phyllosilicate diffraction peaks from the XRD patterns may have been due to the amorphous structure of this species.…”
Section: Xps Analysissupporting
confidence: 85%
“…(3) Table 2). Considering the Co 2p photoelectron spectra for the catalyst precursors, the Co 3 O 4 spinel structure has already been proved to present on the catalyst surface from the typical Co 2p spectrum [15,22]. The electronic properties of cobalt were changed by the incorporation of the additives: the Co 2p 3/2 peaks for all the bimetallic catalysts appeared at higher BE than the peaks for the monometallic catalyst (Fig.…”
Section: Xps Analysismentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, to avoid this problem, carboxylic acids are usually converted into more readily reducible esters. Xue et al [263,264] investigated the use of a bi-functional Ru/TiO 2 catalyst for the conversion of lactic acid or lactates to propylene glycol in the liquid phase. The addition of some additives such as boron, tin, and iron to Ru-based catalysts has been reported in the literature [265].…”
Section: Lactic Acid (La)mentioning
confidence: 99%